Globulin seed storage protein based genotyping and Study of genetic diversity in core accessions of mungbean under drought stress - Tripathy, Swapan Kumar; Mohapatra, Puspak; Prusty, Satya Prakash; Dash, Sasmita; Ranjan, Rajesh; Dash, Gokul Bihari; Senapati, Niranjan; Lenka, Devraj; Mishra, Dayanidhi; Nayak, Pramod Kumar; Swain, Digbijaya; Pradhan, Kedareswar; et al. (Research in Biotechnology, 2015)
Globulin seed storage protein profiles of 19 mungbean genotypes including two wild forms of Vigna radiata var. sublobata(TCR 20 and TCR 213) and two standardÃ‚Â  checks(T 2-1 and LGG 460) were analysed by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). Thirteen genotypes could be clearly identified based on genotype-specific seed protein fingerprints. The combined dendrogram showed six genetic clusters within 68% phenon level. The clustering based on the combined clustering analysis revealed discrimination of all test genotypes even immediately beyond 88% phenon level, whereas individual clustering analysis based on protein and agro-morphological level failed to do so. Nipania munga, TCR 213, T 2-1, LGG 460, TCR 20 and Banapur local B were identified to be highly divergent genotypes. TCR 20 appears to have more genetic proximity to the mungbean genotypes than TCR 213. T 2-1, LGG 460 and TCR 20 are potentially high yielding. These may serve as valuable materials for recombination breeding in mungbean.